1997
DOI: 10.1046/j.1365-2818.1997.1940755.x
|View full text |Cite
|
Sign up to set email alerts
|

Drying cells for SEM, AFM and TEM by hexamethyldisilazane: a study on hepatic endothelial cells

Abstract: SummaryCritical point drying (CPD) is a common method of drying biological specimens for scanning electron microscopy (SEM). Drying by evaporation of hexamethyldisilazane (HMDS) has been described as a good alternative. This method, however, is infrequently used. Therefore, we reassessed HMDS drying. Cultured rat hepatic sinusoidal endothelial cells (LEC), possessing fragile fenestrae and sieve plates, were subjected to CPD and HMDS drying and evaluated in the scanning electron microscope, atomic force microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
214
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(221 citation statements)
references
References 8 publications
3
214
0
1
Order By: Relevance
“…The surface textures of TM in the Lowicryl sections seen here are in agreement with previous studies by scanning electron microscopy of bacterial sections in which specimen-related reliefs of 5-6 nm were found near membranous organelles (Kellenberger et al, 1987). Some of the surface texture of the larger areas of the section observed by AFM at low magnification corresponds to previously published images of sections of cellular regions embedded in different polymeric resins observed using AFM (Yamamoto and Tashiro, 1994;Braet et al, 1997). Previous TEM studies of stained sections of tubular myelin have revealed that some regions of the square lattice networks are more visible than others in the micro- graphs (Gil and Reiss, 1978).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The surface textures of TM in the Lowicryl sections seen here are in agreement with previous studies by scanning electron microscopy of bacterial sections in which specimen-related reliefs of 5-6 nm were found near membranous organelles (Kellenberger et al, 1987). Some of the surface texture of the larger areas of the section observed by AFM at low magnification corresponds to previously published images of sections of cellular regions embedded in different polymeric resins observed using AFM (Yamamoto and Tashiro, 1994;Braet et al, 1997). Previous TEM studies of stained sections of tubular myelin have revealed that some regions of the square lattice networks are more visible than others in the micro- graphs (Gil and Reiss, 1978).…”
Section: Resultssupporting
confidence: 91%
“…A multimodal approach using techniques such as electron and atomic force microscopy on the same macromolecular complex may yield specific three-dimensional information on such systems (Lal and Proksch, 1997). Recent studies using AFM on electron microscopy sections of whole cells have shown that additional information on organelle structures which was not available using either technique by itself, can be obtained (Braet et al, 1997;Canet et al, 1996). The limitations of applying AFM imaging to mixed complex macromolecular systems lie in the somewhat arbitrary identification of the imaged structures, since the three-dimensional surface topography of biological structures may be different from the two-dimensional images obtained using techniques such as transmission electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were dehydrated in graded solutions of ethanol and hexamethyldisilazane (HMDS, Sigma, St. Louis, MO, USA). HMDS has been shown to be as effective at preserving biological sample structure as critical point drying (Braet et al 1997). HMDS was evaporated overnight in a fume hood, and basement membrane samples were stored under desiccant for a minimum of 3 days to ensure complete dehydration.…”
Section: Basement Membrane Isolationmentioning
confidence: 99%
“…Briefly, liver tissue was glutaraldehyde-prefixed, cut to 1 mm 3 samples and following glutaraldehyde fixation, tissue blocks were postfixed in 1% osmium tetroxide and dehydrated in graded ethanol solutions. The liver tissue was then dried with hexamethyldisilazane and subsequently broken in liquid nitrogen, mounted on stubs and sputter coated with a thin layer of 20 nm gold [21] . SEM-samples were examined in a Philips SEM 505 at 30 kV.…”
Section: Liver Tissue Preparation For Light and Electron Microscopymentioning
confidence: 99%